Current Insights into the biochemical and antimicrobial properties of Prosopis farcta plant extract in rats with induced diarrhea - Taha, Intisar Ghanim; Baker, Luma Abd almunim; Ibraheem, Kawakib (Iraqi Journal of Science, 2026)
The research concentrated on developing a water-based extract from Prosopis farcta fruits and analyzing its constituents through Gas Chromatography Mass Spectrometry (GC MS). The study revealed that the plant contains 25 compounds with characteristics based on their molecular structure. The most abundant compound was n Hexadecanoic acid, making up 15,48%, followed by cis 13 Octadecenoic acid at 10,94% and Hexadecanoic acid methyl ester at 10,55%. The impact of the extract properties was measured at a dosage of 200 mg/kg, on animals experiencing diarrhea induced by castor oil for a span of 10 and 20 days of treatment sessions. The results showed that the therapy led to levels of vitamin C and increased activity in the enzyme glutathione peroxidase (GPX) well as enhancements, in insulin and manganese levels. Furthermored, reductions in glucose levels and insulin resistance (HOMA-IR) were observed, alongside a significant decrease in the frequency of daily diarrhea episodes. Additionally, the actived compounds in the extract contributed to repairing liver tissue, by treating necrotic degeneration (cellular swelling) in hepatocytes, reduction in sinusoidal and portal vein congestion, and restoration of normal hepatocyte functions. The extract also reduced inflammatory cell infiltration and tissue congestion in affected areas.